Transición demográfica. Modelos teóricos y experiencia latinoamericana - Perren, Joaquín (Nómadas. Critical Journal of Social and Juridical Science, 2008)
This article visits a tradicional problem of social science: demographic transition. In the first part, it is thought over the theoretical key on this subject matter. Then, it is analyzed the European experience toward the “demographic order”. Finally, one tests a comparison between that one and what happened in Latin America.